(untitled) (Third Sector Social Economic Review, 2025)
This study examines the relationship between ESG performance and intangible asset accumulation using firm-level panel data from 201 telecommunications companies over the period 2003-2023. While ESG strategies are widely believed to enhance firm value by enhancing brand equity, reputation, and stakeholder trust, their impact on intangible assets remains empirically unclear. Drawing on insights from institutional theory and organizational learning theory, this paper examines how this relationship varies with firm age and the strength of the intellectual property (IP) environment. Using random-effects panel regressions with Driscoll-Kraay standard errors, the study finds that ESG scores have an overall negative effect on intangible assets, but this turns positive when moderated by strong intellectual property (IP) regimes. Firm age significantly shapes this relationship. ESG alone has no impact for young firms, yet becomes effective under strong IP protection. For middle-aged firms, ESG is detrimental unless supported by IP environments. In older firms, ESG is slightly beneficial, but the marginal benefit of IP declines. These results highlight that ESG strategies require supportive institutional contexts, especially in early stages, and that firm maturity alters their effectiveness. The study enriches ESG–intangible asset literature through institutional and organizational learning lenses.